2012
DOI: 10.1002/mds.25192
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged hyperechogenic substantia nigra as a risk marker for Parkinson's disease

Abstract: We thus confirm our finding of the 3-year follow-up examination in a longer observation time and higher number of individuals with incident PD and suggest SN+ as an important risk marker for PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 17 publications
8
80
0
4
Order By: Relevance
“…In turn, the triad of SN hyperechogenicity, motor asymmetry and hyposmia is highly predictive for PD already at very early disease stages [32]. The results of several studies underpin the idea that risk scores comprising the finding of SN hyperechogenicity and other risk markers may be valuable in the prediction of subsequent PD [27,32,33]. The recently issued recommendations of the European Federation of Neurological Societies and the European Section of the Movement Disorder Society for the diagnosis of PD state that TCS is recommended (Level A) for: (I) the differential diagnosis of PD from atypical Parkinsonian syndromes and secondary Parkinsonian syndromes, (II) the early diagnosis of PD and (III) the detection of subjects at risk for PD [33].…”
Section: Diagnostic Relevancementioning
confidence: 97%
See 2 more Smart Citations
“…In turn, the triad of SN hyperechogenicity, motor asymmetry and hyposmia is highly predictive for PD already at very early disease stages [32]. The results of several studies underpin the idea that risk scores comprising the finding of SN hyperechogenicity and other risk markers may be valuable in the prediction of subsequent PD [27,32,33]. The recently issued recommendations of the European Federation of Neurological Societies and the European Section of the Movement Disorder Society for the diagnosis of PD state that TCS is recommended (Level A) for: (I) the differential diagnosis of PD from atypical Parkinsonian syndromes and secondary Parkinsonian syndromes, (II) the early diagnosis of PD and (III) the detection of subjects at risk for PD [33].…”
Section: Diagnostic Relevancementioning
confidence: 97%
“…Marked SN hyperechogenicity is also found in about 10 % of healthy adults and has been associated in them with a (subclinical) malfunction of the nigrostriatal dopaminergic system [1,16]. In a 5-year follow-up study performed in Southern Germany and Austria of 1800 subjects at ages between 50 and 70 years without PD at baseline, SN hyperechogenicity was associated with a 20-fold increased risk of developing PD [27]. However, the predictive value of this TCS finding alone is low since more than 80 % of healthy subjects with SN hyperechogenicity will never develop PD during their lifetime [28].…”
Section: Diagnostic Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…After three years of follow up, it was found that 8 out of 10 individuals with incident PD, had SN+ at baseline assessment, indicating a 17-fold increased risk for PD for the participants in this range with SN+ after three years [22]. Extension of the follow-up period to five years increased the relative risk to 20 [23]. This longitudinal study proved that SN+ is indeed a premotor marker for PD.…”
Section: Sn Hyperechogenicity As a Potential Premotor Markermentioning
confidence: 55%
“…TCS shows that 90% of the patients with Parkinson's diseases (PD) have abnormally enlarged SN+ [18]. In addition to PD, corticobasal ganglionic degeneration (CBD), DLB and many other neurodegenerative diseases also have SN+.…”
Section: Discussionmentioning
confidence: 99%